Co-combustion of multilayered plastic waste blend with biomass: Thermokinetics and synergistic effect. (1st April 2023) - Tejaswini, M.S.S.R.; Pathak, Pankaj
Graphical abstract: Highlights: Multilayer plastics and their blends with biomass were characterized. Thermal stability and combustion parameters were determined by thermo-gravimetric analysis. The refuse-derived fuel was optimized to get a higher energy potential. Synergism demonstrates the enhancement of combustion characteristics with the addition of biomass. Abstract: Improper management of inert plastic waste causes severe threats to the environment and leads to global climate change. The thermochemical combustion process adequately converts the plastic waste into a potential energy resource as refuse-derived fuel (RDF), however, to get maximum energy yield, it is required to optimize the combustion process. Therefore, the physio-chemical and thermal characteristics of multilayer plastics (MLPs) and their blends with different biomass are determined under non-isothermal conditions. Five representative samples S1 to S5 which includes MLPs and their blend with biomass were selected for this study. Thermogravimetric analysis was used to perform the combustion process with temperatures ranging from 30 °C to 1000 °C. It is noted that sample S1 has 77.87 % volatile matter, 8.30 % ash content, and 0.01 % sulfur and shows a higher energy potential of 27.10 MJ/kg with minimum environmental emissions, demonstrating good agreement with the RDF I category. Thermo-kinetic parameters using the Coates-Redfern integral method demonstrated that the co-combustion follows a diffusion–reaction mechanism. The sequence of activation energy (Ea ) and Gibbs energy (ΔG) follows in the order of S4  > S5  > S1  > S2  > S3 . Moreover, the maximum Ea and ΔG required for the decomposition of these samples are in the range of 101–142 kJ/mol and 115–120 kJ/mol, respectively. It is concluded that the optimized S1 sample shows similar characteristics to conventional fuels and can be directly co-processed in cement industries or waste-to-energy plants. The obtained results can help in modeling and designing the thermochemical reactor for bench-scale operations.